Efeitos da musicoterapia na qualidade de vida visual de portadores de neurite óptica desmielinizante - Cybelle Maria Veiga Loureiro (2009)
Background: Optic neuritis is an acute inflammatory disease of the optic nerve. Demyelinating optic neuritis (DON) is considered an isolated clinical syndrome because it can occur in the absence of any demyelination of the central nervous system or in association with multiple sclerosis (ON-MS). Visual quality of life (VQL) refers to the subjective perception from patients of their own visual limitations on daily activities. Music therapy (MT) applicability to neurological rehabilitation aims to investigate the effects of musical stimulus perceived orproduced as a mediator stimulus on affective, cognitive, sensorial and motor responses. Research literature on music therapy involving optic neuropathies could not be found on data banks (MEDLINE, LILACS, SciELO and Cochrane). Objectives: To investigate the effects of MT intervention on the VQL of patients with isolated ON or associated to MS and identify which aspects of VQL are more sensitive to the adopted MT approach. Participants and Methods: This is an open pairwise comparative clinical trial not randomized study. The cohort of 40 patients was divided into two equal subgroups, one receiving MT intervention andthe other serving as control. MT experimental tasks included visual-motor, visualspatial and visual-field abilities integrated to music through audition or instrumental execution. Both subgroups were submitted to a ophthalmologic evaluation: visual acuity, biomicroscopy, tonometry, fundoscopy, Low Contrast Sloan Letter, Farnsworth-Munsell 100-hue color vision and Humphrey visual field. The Brazilian version of the National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) was employed to evaluate the VQL in both Groups at the study onset and at the 3rd, 6th, 9th and 12th months in the course of MT. The normality of the sample was verified by Kolmogorov-Smirnov tests. Results: Pairwise comparisons of mean scores of the NEI VFQ-25 showed significant improvement of the Treated Group as compared to Non-Treated Group in the subscales mental health, general health and general vision, at the 6th, 9th and 12th months: p < 0,018, p < 0,043 and p < 0,041 for mental health; p < 0,010, p < 0,037 and p < 0,034 for general health; and p < 0,006, p < 0,051 and p < 0,056 for general vision, respectively. Wilcoxonnon-parametric tests confirmed this statistics. Tendencies of improvement were observed in the Treated Group during 12 month of intervention on all subscales. With the purpose of verifying the improvement of the case group patients, a pairwise comparisons were made. Significant mean differences along the whole treatment were found on subscales of dependency (p < 0,005), general health(p < 0,045), general vision (p < 0,007), mental heath (p <0,001), social functioning (p < 0,009), role difficulties (p < 0,010), distance vision (p < 0,004), near vision (p < 0,007), peripheral vision (p < 0,076), color vision (p < 0,016) and ocular pain (p < 0,022). Conclusion: Results of this study showed that MT produces significant improvement in VQL on patients with history of ON.